2018
DOI: 10.1021/acs.nanolett.8b02190
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Tunable Blue Luminescence of Halide Perovskite Nanoplatelets through Postsynthetic Surface Trap Repair

Abstract: The easily tunable emission of halide perovskite nanocrystals throughout the visible spectrum makes them an extremely promising material for light-emitting applications. Whereas high quantum yields and long-term colloidal stability have already been achieved for nanocrystals emitting in the red and green spectral range, the blue region currently lags behind with low quantum yields, broad emission profiles, and insufficient colloidal stability. In this work, we present a facile synthetic approach for obtaining … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
722
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 437 publications
(795 citation statements)
references
References 50 publications
50
722
3
3
Order By: Relevance
“…Moreover, both pristine and treated NCs exhibit a narrow PL emission with a FWHM of 11 nm, confirming the high uniformity of the NCs. The doping and passivation of the above metal ions can break the restriction of efficiency caused by deep level defects reported by other publications …”
Section: Component Engineering For Blue‐emissive Perovskitesmentioning
confidence: 86%
See 3 more Smart Citations
“…Moreover, both pristine and treated NCs exhibit a narrow PL emission with a FWHM of 11 nm, confirming the high uniformity of the NCs. The doping and passivation of the above metal ions can break the restriction of efficiency caused by deep level defects reported by other publications …”
Section: Component Engineering For Blue‐emissive Perovskitesmentioning
confidence: 86%
“…Moreover, changes in the molar amount of Cs cation can control the thickness of NPL. This is because the thickness of 2D perovskites is determined by the equilibrium of the surfactants and precursors across two phases . The amount of the A‐site cations decreases with respect to the other precursors, limiting the formation of perovskites.…”
Section: Component Engineering For Blue‐emissive Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [15] Other syntheses have expanded this general idea by generating multiple nanocrystal morphologies through ligand mediation [21][22] and reaction tuning, [23] by using different surface ligands for improved quantum yields, [24][25] by increasing surface passivation/repair via salt solutions, [26][27][28][29] as well as by generating other cation/anion compositions through doping [17,[30][31][32][33][34][35] or post-synthetic ion exchange. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%